2019
DOI: 10.1007/s10834-019-09643-1
|View full text |Cite
|
Sign up to set email alerts
|

“Because My Father Told Me To”: Exploratory Insights into Parental Influence on the Retirement Savings Behavior of Adult Children

Abstract: The paper explores the influence of parents on their adult children's retirement saving strategies. Using examples from 25 qualitative interviews the exploratory study shows how financial socialization can continue well beyond adolescence. It offers examples of parents encouraging their adult children to save for retirement and children's reliance upon their parents for advice about pension contribution levels and asset allocation. Parents also provide salient examples-both negative and positive-from which adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 42 publications
3
7
0
Order By: Relevance
“…P04, for instance, grew up seeing his parents prepare budgets at home, but P09 was more influenced by her father’s thrifty and careful spending behaviour, which is now reflected in her own attitude. Such influence, even if indirect, supports the findings of Robertson-Rose (2020), LeBaron et al (2018) and Palaci et al (2017) that parental economic behaviour acts as a positive model for their children’s financial literacies, saving decisions and money-management skills. Spouses and partners influence the participants’ saving behaviour, as do people older than them, specifically colleagues and friends.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…P04, for instance, grew up seeing his parents prepare budgets at home, but P09 was more influenced by her father’s thrifty and careful spending behaviour, which is now reflected in her own attitude. Such influence, even if indirect, supports the findings of Robertson-Rose (2020), LeBaron et al (2018) and Palaci et al (2017) that parental economic behaviour acts as a positive model for their children’s financial literacies, saving decisions and money-management skills. Spouses and partners influence the participants’ saving behaviour, as do people older than them, specifically colleagues and friends.…”
Section: Resultssupporting
confidence: 68%
“…Studies have also investigated the impact of family influence, particularly the influence of parents, on saving behaviour, money management and financial planning for retirement (Robertson-Rose, 2020); LeBaron et al , 2018; Jorgensen et al , 2017; Kagotho et al , 2017; Palaci et al , 2017; Tang, 2017; Grohmann et al , 2015; Tang et al , 2015). In studies involving youths and emerging adults, it was found that when parents and caregivers provide financial instruction to their youths and emerging adults, the youths are more likely to exhibit better saving, money management and other financial behaviours (LeBaron et al , 2018; Kagotho et al , 2017; Jorgensen et al , 2017; Tang et al , 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is due to younger individuals being encouraged by and/or reliant on their parents to give them advice on how to save for retirement. Their parents' attitude towards saving and their saving strategies therefore greatly influenced how the individual went about saving for retirement (Robertson-Rose, 2020). Therefore, the impressionable nature of younger individuals could see them replicating their parent's bad saving techniques.…”
Section: Agementioning
confidence: 99%
“…Concerning to the current study framework, current study has attempted to know the effect of family background, and peer role on saving decisions, peer role and family background are treated as social factors that affects saving decisions. With regard to family background there is categorical and dual nature of parents (positive and negative) (Ribeiro, Fonseca, & Soares 2018;Robertson-Rose 2020). Due to this categorical nature from family, has different effect on saving.…”
Section: Financial Literacy As Mediatormentioning
confidence: 99%